Two Novel Steroidal Alkaloid Glycosides from the Seeds of Lycium barbarum - Wang, Kun; Sasaki, Tatsunori; Li, Wei; Li, Qin; Wang, Yinghua; Asada, Yoshihisa; Kato, Hiroyoshi; Koike, Kazuo (Chemistry & biodiversity, 2011)
Two novel steroidal alkaloid glycosides, lycioside A (1) and lycioside B (2) were isolated from the seeds of Lycium barbarum. Their structures were determined by various spectroscopic analyses. Compounds 1 and 2 showed inhibitory activities with the IC50 values of 75.3 and 72.8 μM against rat intestinal sucrase, and 63.4 and 59.1 μM against rat intestinal maltase.